Analysis of the genotype-phenotype correlation of MYO15A variants in Chinese non-syndromic hearing loss patients - Ying Fu; Shasha Huang; Xue Gao; Mingyu Han; Guojian Wang; Dongyang Kang; Yongyi Yuan; Pu Dai (BMC, 2022)
Abstract Background Mutations in the MYO15A gene are a widely recognized cause of autosomal recessive non-syndromic sensorineural hearing loss (NSHL) globally. Here, we examined the role and the genotype-phenotype correlation of MYO15A variants in a cohort of Chinese NSHL cases. Methods Eighty-one cases with evidenced MYO15A variants from the 2263 Chinese NSHL cases, who underwent next-generation sequencing (NGS), were enrolled in the study. We investigated the association of MYO15A variants with the severity, progression and age of onset of hearing loss, as well as compared it to the previous reports in different nationalities. The cases were divided into groups according to the number of truncating variants: 2 truncating, 1 truncating and 1 non-truncating, 2 non-truncating variants, and compared the severity of HL among the groups. Results MYO15A accounted for 3.58% (81/2263) of all NSHL cases. We analyzed 81 MYO15A-related NSHL cases, 73 of whom were with congenital bilateral, symmetric or severe-to-profound hearing loss (HL), however, 2 of them had a postlingual, asymmetric, mild or moderate HL. There were 102 variants identified in all MYO15A structural domains, 76.47% (78/102) of whom were novel. The most common types of detected variants were missense (44/102, 43.14%), followed by frameshift (27/102, 26.47%), nonsense (14/102, 13.72%), splice site (10/102, 9.80%), in frame (4/102, 3.92%), non-coding (2/102, 1.96%) and synonymous (1/102, 0.98%). The most recurrent variant c.10245_10247delCTC was detected in 12 cases. We observed that the MYO15A variants, located in its N-terminal, motor and FERM domains, led to partial deafness with better residual hearing at low frequencies. There were 34 cases with biallelic truncating variants, 37 cases with monoallelic truncating variants, and 13 cases with biallelic non-truncating variants. The biallelic non-truncating variants group had the least number of cases (12/81), and most of them (10/12) were with profound NSHL. Conclusions MYO15A is a major gene responsible for NSHL in China. Cases with MYO15A variants mostly showed early-onset, symmetric, severe-to-profound hearing loss. This study is by far the largest focused on the evaluation of the genotype-phenotype correlations among the variants in the MYO15A gene and its implication in the outcome of NSHL. The biallelic non-truncating MYO15A variants commonly caused profound HL, and the cases with one or two truncating MYO15A variants tended to increase the risk of HL. Nevertheless, further investigations are needed to clarify the causes for the variable severities and progression rates of hearing loss and the detected MYO15A variants in these cases.